2015
DOI: 10.1016/j.jagp.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Models of Care for Late-Life Depression of the Medically Ill: Examples from Chronic Obstructive Pulmonary Disease and Stroke

Abstract: Depression worsens most treatment outcomes in medically ill older adults. Chronic medical illnesses weaken and demoralize patients and compromise their ability to adhere to treatments requiring consistency and effort. Acute medical illnesses create a psychosocial storm that finds patients and their ecosystem unprepared. We describe two intervention models that can be used to target and personalize treatment in depressed, chronically or acutely medically ill older adults. Personalized Adherence Intervention for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 109 publications
(106 reference statements)
1
7
0
Order By: Relevance
“…The comprehensive life event was estimated with LES, which quantifies the mental stimulation of daily life. This was not entirely in agreement with previous studies of stroke survivors, which reported that comprehensive life event stimulus not a major life event [ 14 , 17 ], and that negative life event [ 18 ] and stressful life event exposure [ 3 , 18 ] was associated with PSD. Regarding personality traits, stable characteristics were assumed to influence the process of creating the illness cognition.…”
Section: Discussionsupporting
confidence: 81%
“…The comprehensive life event was estimated with LES, which quantifies the mental stimulation of daily life. This was not entirely in agreement with previous studies of stroke survivors, which reported that comprehensive life event stimulus not a major life event [ 14 , 17 ], and that negative life event [ 18 ] and stressful life event exposure [ 3 , 18 ] was associated with PSD. Regarding personality traits, stable characteristics were assumed to influence the process of creating the illness cognition.…”
Section: Discussionsupporting
confidence: 81%
“…A patient's ecosystem is important to improving the patient experience and creating wellbeing. For example, ecosystem-focused therapy (EFT) in treating post-stroke depression aims to develop a collaborative approach to motivate the patient and assist the patient and family in developing a rehabilitation plan that includes drawing on community resources (e.g., support groups and recreational services for physically challenged individuals) (Avari & Alexopoulos, 2015). The importance of supporting patients by expanding their ecosystem includes the involvement of family and friends, other patients, access to care and services, and transition and continuity (Gerteis et al, 1993;Jenkinson et al, 2002;Rathert, Brandt, & Williams, 2012).…”
Section: Individual Service Ecosystems and Communitiesmentioning
confidence: 99%
“…Patients who further experience depression face added challenges in their ability to care for themselves and adhere to a demanding medical and rehabilitation regimen [30]. …”
Section: Psychotherapies For Specific Patient Populationsmentioning
confidence: 99%